Pengaruh Rasio Keuangan dan Kebijakan Deviden Terhadap Pertumbuhan Laba (Studi pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Dilyan Ardi Hutama; Moh. Amin; Siti Aminah Anwar (Universitas Islam Malang, 2023)
This study aims to determine the effect of financial ratios and dividend policies simultaneously on profit growth in manufacturing companies listed on the IDX in 2018-2020 with a total population in this study of 59 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2020 years. Profitability which is proxied by Return On Assets (ROE) has a positive and partially significant effect on Profit Growth, Liquidity which is proxied by Current Ratio (CR) has a negative and partially insignificant effect on Profit Growth, Solvency which is proxied by Debt to Equity Ratio (DER) has a negative and not significant effect partially on Profit Growth. Activity proxied by Total Asset Turnover (TATO) has a partially positive and significant effect on Profit Growth, Dividend Policy proxied by the Dividend Payout Ratio (DPR) has a negative and partially significant effect on Profit Growth, Then simultaneously Profitability (ROE), Liquidity (CR), Solvability (DER), Activity (TATO), Dividend Policy (DPR) on Profit Growth (NPM).Keywords: Profitability, liquidity, solvency, activity, dividend policy.